Concurrent gemcitabine and radiotherapy for the treatment of muscle-invasive bladder cancer: A pooled individual data analysis of eight phase I–II trials. Issue 2 (November 2016) - Caffo, Orazio; Thompson, Catherine; De Santis, Maria; Kragelj, Borut; Hamstra, Daniel A.; Azria, David; Fellin, Gianni; Pappagallo, Giovanni L.; Galligioni, Enzo; Choudhury, Ananya
Abstract: Purpose: Although radical cystectomy is still considered the standard of care for most localized muscle-invasive bladder cancer (MIBC) patients, bladder-sparing strategies with chemoradiotherapy have demonstrated comparable local control and survival rates when adjusting for tumor stage. We present a pooled analysis of individual patient data out of published trials with gemcitabine-based chemoradiotherapy for MIBC. Methods and materials: Individual patient data were collected from Institutions that enrolled patients into trials that evaluated gemcitabine-based chemoradiotherapy for MIBC. Results: We identified eight studies published on gemcitabine-based radiochemotherapy and 190 patients were included in this analysis. A complete response (CR) was observed in 166 patients (93%). After a median follow up of 44.5 months, 36 patients (18.9%) presented a bladder recurrence and 14 subsequently underwent cystectomy. The 5-year overall survival (OS), disease-specific survival (DSS), and cystectomy-free survival (CFS) rates were 59%, 80.9%, and 93.3%, respectively. The achievement of CR after chemoradiotherapy was the main prognostic variable which was associated with improved OS, DSS, and CFS. The treatment was well tolerated. Conclusion: This pooled analysis strengthens the evidence that chemoradiotherapy regimens with concurrent gemcitabine are feasible and well tolerated. Prospective randomized controlled trials are on-going to definitively assess the efficacy of gemcitabine-based chemoradiotherapy for MIBC.